Lymphoblastoid cell lines as a model to understand amyotrophic lateral sclerosis disease mechanisms - Pansarasa, Orietta (Dis Model Mech, 2018)
In the past, amyotrophic lateral sclerosis (ALS) has been considered a ‘neurocentric’ disease; however, new evidence suggests that it should instead be looked at from a ‘multisystemic’ or ‘non-neurocentric’ point of view. From 2006, we focused on the study of non-neural cells: ALS patients’ peripheral blood mononuclear cells (PMBCs) and lymphoblastoid cell lines (LCLs). Here, we characterize LCLs of sporadic ALS (sALS) and patients carrying SOD1, TARDBP and FUS mutations to identify an ALS biologically relevant molecular signature, and determine whether and how mutations differentially affect ALS-linked pathways. Although LCLs are different from motor neurons (MNs), in LCLs we found some features typical of degenerating MNs in ALS, i.e. protein aggregation and mitochondrial dysfunction. Moreover, different gene mutations have different effects on ALS cellular mechanisms. TARDBP and FUS mutations imbalance mitochondrial dynamism toward increased fusion, whereas sALS and SOD1 mutations mainly affect fission. With regards to protein aggregation and/or mislocalization, TARDBP and SOD1 mutations show the presence of aggregates, whereas FUS mutation does not induce protein aggregation and/or mislocalization. Finally, all LCLs, independently from mutation, are not able to work in a condition of excessive energy request, suggesting that mitochondria from ALS patients are characterized by a significant metabolic defect. Taken together, these data indicate that LCLs could be a valid cellular model in ALS research in the identification and study of specific pathological pathways.